THE USE OF SPEAKING STATION SITE FOR EFFECTIVE COMMUNICATION IN ESL CLASSROOM - Dashima Abdul Wahab; Amaal Fadhlini Mohamed (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
English language teachers or instructors need changes from time to time. In Malaysia, the focus of English teaching and learning has shifted from accuracy to fluency; the effective usage of the language. Today, students are expected to use the English language in daily communication as well as to learn the workplace English language communication skills. The common speaking lesson in the classroom only requires the students to respond to simple utterances. Thus making some students reluctant to speak. Due to this reason, English language teachers or instructors need to have a solid platform that can guide them in planning and creating better ESL classroom communication. This research was conducted with the aim to help teachers in conducting effective ESL classroom communication. A speaking station site is created to allow English language teachers or instructors to explore their course of action taken in teaching speaking activities after viewing the speaking station site. This speaking station site offers teachers or instructors a guide in the simplest education technology. The site does not require specific payment and almost all can access the link to the platform. The data was collected through interview questions conducted via Google form. Then, it was analysed quantitatively and qualitatively. The results showed English language teachers or instructors are at ease with the speaking station site as it provides guidelines for them to plan effective communication classes properly. Further improvement can be considered in providing a checklist to ensure teachers or instructors evaluate their course of action.